Gender care gap and gender pay gap increase substantially until middle age - Clara Schäper; Annekatrin Schrenker; Katharina Wrohlich (DIW Weekly Report, 2023)
While the gender pay gap between men and women in Germany remains at 18 percent, this figure is not the same for all employees. There are, for example, major differences by age. Beginning at age 30, the gender pay gap increases sharply and remains constantly high at 20 percent until retirement. Closely related to this is the gender care gap, the difference in unpaid care work between women and men. Based on data from the Socio-Economic Panel (SOEP), this Weekly Report shows that the gender care gap also increases up to middle age: At around nine hours per day, women between 35 and 39 perform more than twice as much care work as men of the same age. The time around the birth of a child thus remains decisive for the allocation of unpaid care work and for the wage development of many women. If policymakers want to change this, they must create incentives for a more equal distribution of care work between women and men. Expanding the number of months with parental leave benefits earmarked for each parent could be one starting point. Moreover, a reform of the joint income taxation of married couples (Ehegattensplitting) and the tax subsidies for minijob employees is also long overdue.
Keywords: J31; J16; J22; 330; Gender Pay Gap; Gender Care Gap; Gender Inequality; Family Policy